Embedded Systems and their Vulnerabilities to Hardware Attacks - Konrad Szczepankiewicz; Marian Wnuk (Biuletyn Wojskowej Akademii Technicznej, 2023)
The article describes the types of hardware attacks targeting embedded systems,countermeasures, and methods of modelling security threats. In currently used electronic devices, thesoftware usually ensures very high level of security. On the other hand, hardware implementations, oftenleave vulnerabilities that attackers can use to extract information or disrupt the operation of the device.Being a user of embedded systems, critical for safety, you should be aware of what dangers they maybe exposed to from the hardware side and to know the analysis of the side channel and fault injection.Keywords: hardware attacks, side channel analysis, vulnerabilities of embedded systems, protectionof devices against hardware attacks.